A formação do professor protagonista no Programa Ensino Integral do estado de São Paulo - Pessente, Adriana Maria D'Arezzo (Universidade Federal de São Carlos, 2017)
This research’ objective is to understand the concept of protagonist teacher in the Programa Ensino Integral (PEI) in the State of São Paulo and verifying what formative processes were offered to these teachers in order to constitute them as protagonists. The research intends to answer the following question: How is constitued a protagonist teacher in the Programa Ensino Integral, in order to initiate the implementation of a new educational model? The research participants are teachers working at E.E. Cora Coralina (fictitious name), a state school that joined the Programa Ensino Integral in 2014. The research’ corpus of analysis and interpretation was constituted from mixed questionnaires and semi-structured interview done with the educators working on the program. The research is qualitative and interpretive. It’s build by data triangulation, crossing the information collected from the program's teachers, the Guidelines for the Programa de Ensino Integral do Estado de São Paulo, the literature concerning to the implementation of new educational programs and the oficial documents about the improving processes offered to educators. The results show that the protagonista teacher improving processes offered to the teachers of the program until now wasn’t enought for the program’s requirements. According to the research’ participants, there were no teachers’ improvment offered specifically focused on the protagonism of teachers or related to concepts like leadership and educational autonomy.
Keywords: Protagonista; Autonomia; Liderança; Formação de professores; Protagonist; Autonomy; Leadership; Teacher improvment; CIENCIAS HUMANAS::EDUCACAO